Effects of salivary amylase gene copy number on metabolic health - Sri Lakshmi Sravani Devarakonda; Kalem D. Hanlon; Alex P. Loinard-González; Bethany P. Cummings; Angela C. Poole (Frontiers in Nutrition, 2026)
Precision nutrition is the personalization of dietary recommendations based on characteristics such as genetics, the microbiome, lifestyle, environment, and baseline metabolic state. One potential basis for the development of guidelines is the characterization of gene-diet interactions. In this narrative review, we evaluate the published literature reporting associations between salivary amylase gene copy number and metabolic health. The salivary amylase enzyme facilitates starch digestion and is encoded by AMY1 , a gene copy number (CN) variant. Humans have 2–20 copies, and AMY1 CN has been associated with metabolic health conditions such as obesity and insulin resistance. Studies of these associations have conflicting findings. The objectives of this review are to assess the findings from studies testing associations between AMY1 CN and adiposity, glucose metabolism, and gut microbiome composition; to explore possible mechanisms underlying the effects on metabolic health; and to identify knowledge gaps requiring additional research. To identify relevant articles, we searched PubMed, Web of Science, Cumulative Index to Nursing and Allied Health Literature, and Centre for Agricultural and Biosciences International for articles focused on AMY1 CN and one or more of the following: body mass index, glucose metabolism, and the microbiome. Key findings are that AMY1 CN has a positive association with postprandial glucose response and that a high AMY1 CN is protective against insulin resistance. AMY1 CN alone does not appear to be an accurate predictor of adiposity, and the relationship is likely convoluted by habitual starch intake, genetic background, and lifestyle factors. Future studies are required to determine how AMY1 CN could be used as a biomarker or to inform precision nutrition protocols to achieve metabolic health outcomes.